Wood pallet projects : cool and easy-to-make projects for the home and garden - Gleason, Chris, 1973- (Fox Chapel Publishing, 2013)
"Lumber prices are soaring, and deforestation is a rising concern. Yet millions of pounds of perfectly usable wood are dumped in landfills every year. Wood Pallet Projects shows how anyone can upcycle salvaged pallet wood to create truly one-of-a-kind projects. Maverick craftsman Chris Gleason combines sound woodworking techniques with a hip designer's sensibility to unleash the limitless possibilities of the common skid. Inside you'll find 15 of his inspired projects for rescuing and repurposing pallets. Some of his pieces celebrate the rough, edgy character of the material, while others are crafted as fine furniture. He shows how to construct both indoor and outdoor furniture in a variety of styles, along with other useful items such as a birdhouse, a toolbox, and even a ukulele. There's plenty of nitty gritty here on working with pallets, including where to find them, how to process them into usable lumber, fasteners, sanding, and the best finishes (if any) to use. The author provides important advice on how to make sure that your pallets are safe, and not sprayed with harmful chemicals. A colorful gallery of finished work provides further inspiration for green crafting"--